PERSEPSI MAHASISWA TERHADAP PROFESIONALISME DOSEN DI LINGKUNGAN PERGURUAN TINGGI SWASTA DI SURAKARTA - Wenny Anggraeni Puspa Dhewi, Hernawati Pramesti & (Universitas Slamet Riyadi, 2006)
ABSTRACT Â This study aimed to provide emperical about perception university student to impact profesionalisme lecturer in University in Surakarta. Take the sample use purposive random sampling and conveniance sampling. Total respondent were 40 respondents. Then, the data was measure with 4 factor profesionalism, is skill, knowledge, attitue, and ethics.Analyzed using proporsions, score and chy-square. The study result indicated that skill factor value of means is 3,4. Knoelwdge factor value of means is 3,5, attitude factor value of means is 3,335 and ethics factor value of means is 3,465. So the conclusion tis study that perception university student to impact profesionalisme lecturer in University in Surakarta good. Keywords: Perception, professionalism, skill, kowledge, attitude and ethics